COMMUNICATION INNOVATION BASED ON PSYCHOLOGICAL CHARACTERISTICS TO INCREASE DEVELOPMENT PARTICIPATION OF THE BAJAU TRIBE IN INDONESIA - Junuda1*, Usman Rianse2, Weka Widayati3, Nani Yuniar4, and Hasddin5 (Chelonian Research Foundation, 2023)
This research aims to develop a development communication innovation model based on psychological and spiritual characteristics including individual characteristics, personality, and clinical syndromes in an effort to increase their participation in the development process. This study takes a case as a differentiator from my previous study, namely the Bajau tribe community in Soropia District, Konawe Regency, Southeast Sulawesi Province, Indonesia. Research, using a quantitative paradigm with survey design methods (research design). The research sample was 251 Bajau tribes determined using Proportional Cluster Random Sampling to select a representative sample. Data collection was carried out using questionnaires and the Millon Clinical Multiaxial Inventory IV (MCMI IV) application to identify the psychological characteristics of respondents as a basis for developing spiritual intelligence. Apart from that, document studies were also carried out to understand the development context and conditions of the Bajo Soropia tribe. Data analysis was carried out using descriptive statistics and statistical analysis with SEM-PLS. It was found that the individual characteristic that has the strongest influence in determining development participation is the level of education. Then the highly determined personality (strong influence) is Schizotypal, followed by Melancholic, Dependent, Anti-social, Sadistic, Negativistic, Borderline, and Paranoid. The clinical syndrome indicator that has the strongest influence in efforts to increase Bajau participation in development is delusional disorder, followed by other indicators such as major depression, somatic symptoms, drug use, anxiety, and alcohol use. Keywords: Communication innovation, psychological-characteristics, spritual development participation